A Relational Comparison: The Gendered Effects of Cross-Border Work in Palestine within a Global Frame. Issue 6 (18th August 2022) - Griffiths, Mark; Brooks, Andrew
Abstract : This article sets the gendered effects of low-wage, cross-border labor in Palestine within a global frame of uneven development. Drawing on fieldwork close to Checkpoint 300, between Bethlehem and Jerusalem, we first provide an account that centers Palestinian women's social reproduction as coconstitutive of male cross-border employment in the Israeli economy. Discussion then moves to consider gendered work in apartheid-era South Africa with the intention not to draw analogies but to explore how labor articulation situated South Africa within the power geometries of globalization. Returning with these analytical tools, we undertake a relational comparison to reconsider the cross-border as a global space. Cutting-edge security technologies and migrants from Thailand are some of the new objects, ideas, and people that coalesce and reshape Palestinian domestic life. The gendered effects of social reproduction are thus connected to both Israel's military occupation and its location within global capitalism. The article makes three key contributions by (1) foregrounding women in discussion of cross-border labor, (2) explicating state–global relations in regimes of segregation, and (3) mobilizing relational comparison as a tool for understanding local exploitation within global structures.